Hints for panmixia in Scomberomorus commerson in Indian waters revealed by mitochondrial ATPase 6 and 8 genes. (3rd July 2016) - Vineesh, N.; Kathirvelpandian, A.; Divya, P. R.; Mohitha, C.; Basheer, V. S.; Gopalakrishnan, A.; Jena, J. K.
Abstract: Scomberomorus commerson is an economically important migratory fish distributed worldwide. The genetic stock structure of S. commerson distributed along the Indian waters was identified using mitochondrial ATPase 6 and 8 genes. A total of 842 bp sequence of ATPase 6/8 genes obtained in this study revealed 23 haplotypes with mean low nucleotide diversity and high haplotype diversity. Co-efficient of genetic differentiation ( F ST ) values obtained for pair wise populations were low and non-significant with an overall value of −0.02074. The high haplotype and low nucleotide diversity values together with mismatch distribution analysis suggested a history of genetic bottleneck events or founder effect, with subsequent population expansion in S. commerson. The findings of the present study indicated the panmixia nature of the species which can be managed as a unit stock in Indian waters.